Provider bias and family planning in Upper Egypt: a simulated client approach - Mirette M. Aziz; Amira F. El-Gazzar (SpringerOpen, 2023)
Abstract Background Provider bias is a main barrier that extensively violates the right of free family planning method choice. Egypt is one of the countries that shows skewness in its method mix. Provider bias and insufficiency of alternative methods are identified as potential factors underlying this phenomenon which contributes to high unmet needs and discontinuation rates. Provider bias may be influenced by cultural beliefs and societal trends and is usually overlooked as a possible cause of this skewed method mix. This study aims to explore the presence of provider bias in rural Upper Egypt and its potential causes, a community with conservative cultural beliefs and least contraceptive prevalence rates. Methods This is a qualitative study using the "simulated client's approach." The study was conducted in 16 villages in Assiut and Sohag governorates in Egypt. The simulated clients visited 30 clinics, 15 in each governorate, including primary healthcare units and private clinics. Three scenarios were used to explore the physicians-imposed restrictions for contraceptive use with different clients' eligibility criteria. Data was analyzed using the grounded theory methodology. Results Recommending a contraceptive method for the mystery clients was not based on informed choice. Most providers had method or client bias. Copper IUD was the most favorable contraceptive method recommended by providers, with negative attitude towards using hormonal contraception. Nulliparous and young clients were discouraged to use contraception before proving fertility or offered temporary methods as emergency contraception or condoms. Providers have shown misconceptions related to infertility-associated complications of contraceptive use, especially for the young and nulliparous women. Conclusion In this study, providers had a clear bias towards recommending IUD rather than all other contraceptive methods, which was hindered in some cases by the lack of insertion skills. Interventions to reduce provider bias should go beyond technical training. Moreover, training on reproductive rights should be a main component of routine training. Providers should regularly receive research results and be oriented toward recent medical eligibility criteria of contraceptive methods use. Moreover, the sociocultural beliefs of providers that may affect their practice should be explored and addressed.